Strategi Pemasaran Dengan Memanfaatkan Sosial Media Pada Perusahaan Ikifarm Hidroponik, Kabupaten Bogor: Marketing Strategy Using Social Media at Ikifarm Hydroponics Company, Bogor Regency - Ayutyas Sayekti; Putri, Meiriskha Eka; Makarim, Muhammad Nauval (IPB University, 2023)
IkiFarm Hydropnics is a company engaged in the cultivation of hidroponik plants by producing vegetable products. There is a problem that the company produces a higher amount of production compared to the amount of product sales. Over supply has an impact on the condition of vegetables for too long on planting or past the harvest period, resulting in a decrease in the quality of vegetables, making it difficult to get consumers, which will harm the company. So there is a need for a new market so that vegetables sell well and increase revenue for the company. The purpose of this study is to formulate a marketing strategy to increase revenue at the IKIFarm Hydroponic company supported by analysis of nonfinancial aspects and financial aspects. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with management and expert respondents. The results of the research provide an overview of IKIFarm Hydroponic's business conditions in the form of market expansion by optimizing the company's Instagram social media for consumers in Jabodetabek. Based on the financial aspect of using an income statement with the resulting profit of Rp 155,945,355 and the R/C Ratio increased to 1.48. Meanwhile, the non-financial aspect uses market and marketing aspects, production aspects, management and organizational aspects, human resources aspects, and collaboration aspects are said to be feasible. Marketing strategies implemented by utilizing digital marketing can absorb the market and have an impact on maximizing marketing, reducing the accumulation of vegetables that are not sold well and increasing revenue for the company ABSTRAK IkiFarm Hydroponik merupakan perusahaan yang bergerak pada bidang budidaya tanaman hidroponik dengan menghasilkan produk sayuran. Terdapat permasalahan bahwa perusahaan menghasilkan jumlah produksi lebih tinggi dibandingkan dengan jumlah penjualan produk. Over supply berdampak pada kondisi sayuran terlalu lama pada penanaman atau melewati masa panen maka mengakibatkan penurunan kualitas sayuran hal tersebut membuat sulitnya mendapatkan konsumen sehingga akan merugikan perusahaan. Maka perlu adanya pasar baru agar sayuran laku terjual serta meningkatkan pendapatan bagi perusahaan. Tujuan penelitian ini adalah merumuskan strategi pemasaran untuk meningkatkan pendapatan pada perusahaan IKIFarm Hidroponik dengan didukung analisis aspek nonfinansial dan aspek finansial. Data yang digunakan dalam penelitian ini adalah data primer dan data sekunder. Data primer diperoleh melalui wawancara langsung dengan pihak manajemen dan responden ahli. Hasil penelitan memberikan gambaran tentang kondisi bisnis IKIFarm Hidroponik berupa perluasan pasar dengan melakukan optimalisasi sosial media instagram perusahaan untuk konsumen yang berada di Jabodetabek. Berdasarkan aspek finansial menggunakan laporan laba rugi dengan keuntungan yang dihasilkan adalah Rp 155.945.355 dan R/C Ratio meningkat menjadi 1,48. Sedangkan aspek non finansial menggunakan aspek pasar dan pemasaran, aspek produksi, aspek manajemen dan organisasi, aspek sumberdaya manusia,dan aspek kolaborasi dikatakan layak. Strategi pemasaran yang diterapkan dengan memamnfaatkan digital marketing dapat menyerap pasar dan berdampak pada memaksimalkan pemasaran, mengurangi penumpukan sayuran yang tudak laku terjual serta menambah pendapatan bagi perusahaan.